Rule of wolves - Bardugo, Leigh (King of scars duology, 2021)
As Fjerda's massive army prepares to invade, Nikolai Lantsov will summon every bit of his ingenuity and charm to win this fight, and Zoya Nazyalensky must embrace her powers to become the weapon her country needs, meanwhile Nina Zenik risks discovery and death as she wages war on Fjerda from inside its capital.